A Study on the Phenomenon of Land Use Change in the Suburbs (Urban Periphery) of Medan City and Its Influence on the Spatial Pattern Plan Case Study of Medan Marelan District - Mas Pratono; Feby Milanie; Abdi Sugiarto (International Journal of Society and Law, 2024)
This study aims to analyze land use changes in Medan Marelan District in 2004, 2014, and 2024 and identify the suitability of existing land use with the Medan City Regional Spatial Plan (RTRW) policy. The research method used is qualitative descriptive with a spatial approach based on Geographic Information System (GIS). Data was collected through primary and secondary surveys, including satellite imagery, administrative maps, and demographic data. The results of the study showed that there was a significant change in land use in Medan Marelan District during the study period, especially the increase in residential and industrial areas. The superimpose analysis shows that most of the existing land use is in accordance with the RTRW, although there are some irregularities. Factors such as the number of population, land value, distance to the city center, and the number of public facilities contribute significantly to the development of the area. In accordance with the results of the SWOT analysis, there are several strategies in this study, one of which is utilizing the power of technology and data to design a more accurate and sustainable spatial plan policy that considers the history of the area in Medan Marelan District. The conclusion of this study is the importance of Regional Space (RTRW) periodically to effectively manage the development of peri-urban areas. It is also recommended that there be community involvement in spatial planning to increase the suitability of land allocation with the Regional Spatial Plan policy.